Haematological Effect of Tridax Procumbens Methanolic Extract in Wistar Rats - Ngaski, A.A.*, Abubakar, M. and Bunza, F.U. (Sokoto Journal of Medical Laboratory Science)
This study seeks to assess the haematological effect of Tridax procumbens methanolic extract (TPME) in Wistar rats. Tridax procumbens is a common procumbent plant with several therapeutic potentials. Forty (40) Wistar rats divided into two (2) sets of twenty- one (21) and eighteen (18) were used. The set of twenty-one(21) rats was used to carryout the acute oral toxicity of the TPME to obtain the LD50 of the extract using the Lorke’s method. The set of eighteen (18) rats was divided into six (6) groups of three (3) rats each. Rats in the first group served as the normal control and received 0.5 mL of distilled water. Rats in the remaining five (5) groups received 50 mg/kg, 100 mg/kg, 200 mg/kg, 400 mg/kg and 800 mg/kg of TPME per body weight for twenty-eight (28) consecutive days respectively. Haematological indices of blood such as PCV, HCT, HGB, MCH, MCHC, MCV, WBC, LYM, NEUT, MXD and PLT were measured in the blood sample to evaluate the effect of the extract in the exposed animals. Statistical analysis using ANOVA and Tukey post hoc test was done for all parameters measured. Change in weight of the exposed animals reduced, albeit non-significant (p>0.05). There was a significant increase in neutrophils count, with the highest effects produced by groups that received 400 mg/kg and 800 mg/kg of TPME. There was a non-significant increase of PCV, HCT, HGB, MCH, MCHC and MCV across the group as well as a non-significant decrease in RBC, WBC, MXD and lymphocytes counts across the groups (p>0.05). In summary, the result from this study indicates that the administration of TPME may possess some haematinic effect and as such can be investigated further for potential use as a haematinic agent.